Modern Linguistic Reviews of Arab Declension and its Educational Dimensions - Boudrama, Zaidi; Soucha, Lameri (Journal of Human Sciences, 2021)
This paper aims to identify the most important difficulties that characterized the old Arab morphological lesson, then to review the most important criticisms and alternatives suggested by the modern Arab linguists, and to know its dimensions in facilitating learning declension. so What are these criticism? What are their references? and what are suggested Alternatives? We have come to the conclusion that the difficulty of Arab declension is due to several things, including: assumption and interpretation, frequent abstractions, and dependence on dual origin and branch, among others. Modern linguists have proposed to avoid a variety of alternatives that can be invested in facilitating declension education, including: focusing on what serves the composition, looking at each formula independently so that we do not get into the maze of interpretation and appreciation, and confine the abstract to the trio only.